Analisis Manajemen Utang Terhadap Penilaian Risiko Kinerja Keuangan Pemerintah Daerah Kota Magelang Tahun 2021-2022 - Nicodemus Christian Aribowo; Amanda Yulia Damayanti; Risma Wira Bharata (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2023)
Debt management is a complex process in managing the finances of a local government that requires analysis of its financial performance risks. The aim of this study is to evaluate the financial performance risks in the Magelang City Local Government and analyze the debt management practices used by the Magelang City Local Government. This study used a descriptive analysis method to determine the debt management analysis used to assess the financial performance risks of the Magelang City Local Government. The results of the study indicate that the effectiveness ratio is categorized as effective, the efficiency ratio is categorized as less efficient, the independence ratio is still low, the activity ratio has increased, and the growth ratio is categorized as having increased. This study is expected to contribute to the Magelang City Local Government in providing information to relevant parties who need the results of this study as an indicator in decision making.